The illiquidity premium: International Evidence - Amihud, Y.; Hameed, A.; Kang, W.; Zhang, Huiping (Elsevier, 2014)
Examining the illiquidity premium in stock markets across 45 countries, we find the following. First, the average illiquidity return premium across countries is positive and significant, after controlling for other pricing factors. The premium is measured by monthly return series on illiquid-minus-liquid stocks or by the coefficient of stock illiquidity estimated from cross-section Fama-MacBeth regressions. Second, there is a commonality across countries in the illiquidity return premium, controlling for common global return factors and variation in global illiquidity. This commonality is different from commonality in illiquidity itself and is greater in globally-integrated markets.